Penatalaksanaan Fisioterapi Pada Kasus Ischialgia Karena Spondylosis Lumbal L4 - L5 Di Pku Muhammadiyah Yogyakarta - Isyanatungga, Endingtyas; , Maskun Pudjianto, SMPH, M.Kes (2015)
Background: ischialgia is a disease of the nerve disorder characterized ischiadicus severe pain in the lower back and hamstrings radiating pass to the feet. Spondylosis are degenerative changes at the lumbosacral spine that can occur in the vertebrae. Objective: To determine the treatment of physiotherapy in reducing pain, improving LGS, spasms, and muscle strength in case ischialgia due to lumbar spondylosis using TENS modalities and wiliam flexion exercise. Results: After treatment 6 times the result of a silent pain assessment T1: 1.2 to T6: 0, painful motion of Tl: 4.6 to T6: 3.7 and tenderness T1: 3.2 into T6: 2 , 7. Increased LGS, LGS The left lateral flexion T1: 7 becomes T6: 8 in flexion T1: 3 to T6: 4 and extension movements of T1: 3.5 into a T6: 4. A decrease in T1 spasm spasm namely: there, T2: still there, T3: there, T4: is reduced, T5: reduced, and T6 : reduced. MMT increase in lumbar flexors of T1: 2 to T6: 3. Evaluation of functional activity there is an increase of T1: moderate dependence, becomes T6: dependency moderate / minimal disability. Conclusions: TENS can reduce pain in the lower back in the case ischialgia, William flexion exercise can improve lumbar LGS, decrease spasms in the lumbar, and increase muscle strength. Keywords: TENS (Tranascutaneus Electrical Nerve Stimulation), LGS (range of motion), MMT (Manual Muscle Testing).